The Different Roles of 5-HT2 and 5-HT3 Receptors on Antinociceptive Effect of Paroxetine in Chemical Stimuli in Mice - Murat Kesim; Erdem N. Duman; Mine Kadioglu; Ersin Yaris; Nuri I. Kalyoncu; Nesrin Erciyes (Elsevier, 2005)
Serotonin (5-HT) is known to be an important mediator in pain modulation. Some centrally acting agents, like selective serotonin reuptake inhibitors (SSRIs), modulate pain. Activation of the endogenous opioid mechanisms or potentiation of analgesic effect by serotonergic and/or noradrenergic pathways might be involved in antinociception of SSRIs. However, peripheral mechanisms of nociception are not clear. In this study, the antinociceptive effect of paroxetine, its interaction with the opioidergic system and serotonin receptors were tested using the writhing test in mice. Paroxetine (5, 10, 20 mg/kg) induced an antinociceptive effect following i.p. administration in writhing test. For the groups in which the antagonists were tested, the dose of paroxetine that caused a significant and equipotent analgesic effect similar to 0.5 mg/kg morphine was selected. Naloxone significantly antagonized the antinociceptive effects of both paroxetine and morphine in a similar pattern and magnitude. Ketanserin (5-HT2-receptor antagonist) or ondansetron (5-HT3-receptor antagonist) alone did not alter the nociceptive action of acetic acid. While the antinociceptive effect of paroxetine was highly potentiated by ketanserin, ondansetron reduced that antinociception. In conclusion, our results indicate that the antinociceptive effect of paroxetine mainly depends on central opioidergic and serotonergic mechanisms. Peripheral serotonergic mechanisms/receptors may contribute to this antinociceptive effect, especially by 5-HT3-receptor subtypes. Keywords:: paroxetine, nociception, writhing test, 5-HT receptor subtype